Issues of cadastral maps updating and accuracy for establishing GIS databases of detailed urban plans - Radovan ĐUROVIĆ; Gojko R. NIKOLIĆ (Micro, Macro & Mezzo Geoinformation, 2018)
Cadastral map, when the Real Estate Cadastre is being produced, initially contains the boundaries of cadastral parcels, buildings, and cultures. After the formation of the Real Estate Cadastre, under the procedure cadastral maintenance, all changes on real estate which are taking place on the ground are being registered; however, the registration is not done ex officio by the administrative authorities. Practice has shown that property rights holders fail to report a vast number of changes that occurred in relation to the registered status in the cadastre to the administrative authority in a timely manner. A particular problem are the differences between areas in graphical and textual GIS database, and all of the issues above represent a major issue in the case of adoption of cadastral maps as conditionally accurate for the creation and implementation of detailed urban plans. The issue persists in operative cadastre over the entire territory of Montenegro, with its emergence and solution being analyzed in detail on the example of the Municipality of Bar.